Product market competition, corporate governance and firm performance: an empirical analysis for Germany - Silke I. Januszewski; Jens Köke; Joachim K. Winter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
Productivity growth has been slow in many continental European countries over the last few decades, especially in comparison with the United States. It has been argued that lack of product market competition and poor corporate governance are two of the main reasons for this phenomenon. However, predictions from theoretical models are far from unambiguous, and empirical evidence is sparse, in particular at the level of individual firms. In this paper, we aim to close this gap with an econometric analysis of firm performance in Germany. Based on a unique panel data set with detailed information on almost 400 manufacturing firms over the 1986-94 period, we find that firms operating in industries which are characterized by more intensive product market competition experience higher rates of productivity growth. We also find weak evidence for the notion that in Germany?s bank-based system of internal control, ownership concentration is harmful for productivity growth.
Keywords: D43; D24; G32; 330; competition; corporate governance; productivity; Produktivität; Unternehmensentwicklung; Wettbewerb; Corporate Governance; Cobb-Douglas-Produktionsfunktion; Schätzung; Vergleich; Deutschland; USA